Construction of Epistemological Interpretation on Eschatology Verses In ‘Aisyah ‘Abdurrahman al-Syati’s Perspective - Taufiqurrahman Taufiqurrahman; Resya Farasy Naffasa (Jurnal Ushuluddin, 2020)
This study aims to examine the perspective of ‘Aisyaḧ ‘Abdurrahman al-Syati’ (1913-1998), as a contemporary female mufassir, regarding eschatological verses in surah al-Zalzalaḧ to prove the epistemological construction of interpretations based on sources, methods and validity of truth. The object of this research is the text and its relationship with past events, that a literature study is carried out to learn content analysis using a historical approach. The primary data in this study is the book of Tafsyr al-Bayany and supported by literature on the epistemology of interpretation in a philosophical approach. The results revealed that ‘Âisyah ‘Abdurrahman has interpreted surah al-Zalzalaḧ referred to Arabic language grammar, the prophet’s hadith, and previous interpretations. In the epistemology of interpretation, the verses about eschatology are not sufficient if they are interpreted in language separately, despite proving the validity of interpretive coherence, she remains consistent in using those  method, even correspondingly the interpretation of zilzal is a picture of the earth’s condition when it shakes in accordance with the reality and scientific facts about earthquake, as well as in line with the argument about a doomsday that is bound to happen as found in terms in the Qur’an.